Engineering gold shelled nanomagnets for pre-setting the operating temperature for magnetic hyperthermia - Siqueira, Elis Regina Lima (2022)
This study investigated the fabrication of spherical gold shelled maghemite nanoparticles for use in magnetic hyperthermia (MHT) assays. A maghemite core (14 ± 3 nm) was used to fabricate two samples with different gold thicknesses, which presented gold (g)/maghemite (m) content ratios of 0.0376 and 0.0752. The samples were tested in MHT assays (temperature versus time) with varying frequencies (100–650 kHz) and field amplitudes (9–25 mT). The asymptotic temperatures (T∞) of the aqueous suspensions (40 mg Fe/mL) were found to be in the range of 59–77 ◦C (naked maghemite), 44–58 ◦C (g/m = 0.0376) and 33–51 ◦C (g/m = 0.0752). The MHT data revealed that T∞ could be successful controlled using the gold thickness and cover the range for cell apoptosis, thereby providing a new strategy for the safe use of MHT in practice. The highest SAR (specific absorption rate) value was achieved (75 kW/kg) using the thinner gold shell layer (334 kHz, 17 mT) and was roughly twenty times bigger than the best SAR value that has been reported for similar structures. Moreover, the time that was required to achieve T∞ could be modeled by changing the thermal conductivity of the shell layer and/or the shape/size of the structure. The MHT assays were pioneeringly modeled using a derived equation that was analytically identical to the Box–Lucas method (which was reported as phenomenological).